Analysis and Synthesis of Switched Time-Delay Systems: The Average Dwell Time Approach - Zhang, Dan.; Yu, Li.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book, written by experts in the field, is based on the latest research on the analysis and synthesis of switched time-delay systems. It covers the stability, filtering, fault detection and control problems, which are studied using the average dwell time approach. It presents both the continuous-time and discrete-time systems and provides useful insights and methods, as well as practical algorithms that can be considered in other complex systems, such as neuron networks and genetic regulatory networks, making it a valuable resource for researchers, scientists and engineers in the field of system sciences and control communities. .
Introduction to switched time-delay systems -- Fundamentals to stability, filtering and control -- Exponential stability of switched time-delay systems -- Passivity analysis of switched time-delay systems -- Filtering of continuous-time switched time-delay systems -- Filtering of continuous-time stochastic switched time-delay systems -- Filtering of discrete-time stochastic switched time-delay systems -- Asynchronous filtering of continuous-time switched time-delay systems -- Asynchronous filtering of discrete-time switched time-delay systems -- Filtering of discrete-time singular switched time-delay systems -- Fault detection of discrete-time switched time-delay systems -- Stabilization of continuous-time switched time-delay systems -- Fault tolerant control for discrete-time switched time-delay systems -- Finite-time control for discrete-time switched time-delay systems.
Keywords: Control engineering; System theory; Control theory; Electronic circuits; Control and Systems Theory; Systems Theory, Control; Electronic Circuits and Systems